2020
DOI: 10.1371/journal.pone.0231332
|View full text |Cite
|
Sign up to set email alerts
|

Does quality of life return to pre-treatment levels five years after curative intent surgery for colorectal cancer? Evidence from the ColoREctal Wellbeing (CREW) study

Abstract: BackgroundThe ColoREctal Wellbeing (CREW) study is the first study to prospectively recruit colorectal cancer (CRC) patients, carry out the baseline assessment pre-treatment and follow patients up over five years to delineate the impact of treatment on health and wellbeing. MethodsCRC patients received questionnaires at baseline (pre-surgery), 3,9,15,24,36, 48 and 60 months. The primary outcome was Quality of Life in Adult Cancer Survivors (QLACS); selfefficacy, mental health, social support, affect, socio-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 37 publications
(50 reference statements)
0
46
0
Order By: Relevance
“…Quality of Life (QoL) is complex; it is highly individual, influenced by values, expectations and cultures, manifesting in an individuals' perception of their physical, psychological, social and functional well-being [1,2]. Colorectal cancer (CRC) survivors' QoL may improve over time, and for some, may reach levels that are comparable to normative populations and pre-diagnosis [3][4][5]. Despite this, a substantial proportion of CRC survivors may experience distressing physical, psychological and social effects, persisting for years beyond diagnosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of Life (QoL) is complex; it is highly individual, influenced by values, expectations and cultures, manifesting in an individuals' perception of their physical, psychological, social and functional well-being [1,2]. Colorectal cancer (CRC) survivors' QoL may improve over time, and for some, may reach levels that are comparable to normative populations and pre-diagnosis [3][4][5]. Despite this, a substantial proportion of CRC survivors may experience distressing physical, psychological and social effects, persisting for years beyond diagnosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to CRC, findings are similar, with HRQoL dropping significantly below the preoperative values one month following the surgery and fatigue being identified as the most troublesome problem 1 and 5 weeks postoperatively [ 6 ]. Regarding long-term recovery, approximately 40% of the patients reported a worse HRQoL 6 months after surgery and about one-third did not return to pre-surgery levels five years after treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when aiming to improve patient-centered care, where the individual’s perspective is emphasized, it becomes important to find interventions that could enhance HRQoL and reduce fatigue severity following CRC and LC resections [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow of participants through the study has been reported elsewhere. 54 A total of 872 people provided full consent, with response rates between 88% at baseline and 71% at 60 months. Of the consented participants, 790 had a sexual well-being outcome on at least one time point throughout the study and are included in table 1 (baseline characteristics), and figure 1 (prevalence of poor sexual well-being).…”
Section: Participantsmentioning
confidence: 99%